Reduced-fluence photodynamic therapy and anti-vascular endothelial growth factor for polypoidal choroidal vasculopathy in an Indian population - Sen, Parveen (Indian J Ophthalmol, 2016)
AIMS: The aim was to study the efficacy of combined therapy with reduced-fluence photodynamic therapy (RFPDT) and intravitreal bevacizumab/ranibizumab from the Indian subcontinent. SETTINGS AND DESIGN: This was a single-center, retrospective interventional study. METHODS: Thirty-five eyes of 34 patients diagnosed with polypoidal choroidal vasculopathy were included. All the patients underwent RFPDT, followed by intravitreal bevacizumab/ranibizumab. STATISTICAL ANALYSIS USED: SPSS software, version 17.0 (SPSS Inc., Chicago, IL, USA) was used to compare the logarithm of the minimal angle of resolution visual acuity at presentation and final follow-up. P < 0.05 was considered statistically significant. RESULTS: Regression of polyps after a single session of RFPDT was seen in five eyes; multiple sessions of treatment were required in thirty eyes. An average number of intravitreal anti-vascular endothelial growth factor (anti-VEGF) injections given were 4 ± 1.9 and average number of PDT sessions were 1.2 ± 0.5. Visual acuity improvement was seen in 21 (60%) eyes (P < 0.001), decrease in visual acuity was seen in 7 (20%) eyes (P = 0.016), and in 7 eyes (20%), vision remained stable. Regression of polypoidal lesions was seen in 80% of cases. No complications of massive subretinal hemorrhage or breakthrough vitreous hemorrhage were noted in our patients. The mean follow-up period was 18 months (range, 12–24 months). CONCLUSIONS: RFPDT with anti-VEGF is safe and effective treatment with polyp regression and vision improvement in 80% of cases, without any complication of subretinal hemorrhage/vitreous hemorrhage.